2012
DOI: 10.1002/icd.1752
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Sleep–Wake Regulation and Attachment Security with Parents

Abstract: The development of sleep-wake regulation occurs within the context of the infant-parent relationship. The present study investigated (1) patterns of change in night waking across infancy and attachment to parents and (2) if dependency, a characteristic of secure subgroup B4 and insecure-resistant infants, accounted for differences in night waking. Forty-six families reported on the number of infant night wakings at 7, 12, and 14 months of age. Attachment was measured at 12 (infant-mother) and 14 (infant-father… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Such unpredictability might play a reinforcing role for child signaling or even amplification of distress during nighttime separations. This would not only translate into concurrent maternal reports of poorer sleep quality among dependent (Scher & Asher, ) or resistant infants (Beijers et al, ; McNamara et al, ; Zentall et al, ), as often observed, but also, as suggested by the current results, could play a causal role in the unfolding of real sleep difficulties among these children, who may become increasingly less able to self‐regulate at night without the intervention of a caregiver (Sadeh et al, ). Hence, although our findings are clearest in the suggestion of a role for secure parent‐child attachment in the development of adequate sleep regulation among toddlers, we would tentatively suggest that child dependency generally, or resistant attachment specifically, may deserve further attention.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Such unpredictability might play a reinforcing role for child signaling or even amplification of distress during nighttime separations. This would not only translate into concurrent maternal reports of poorer sleep quality among dependent (Scher & Asher, ) or resistant infants (Beijers et al, ; McNamara et al, ; Zentall et al, ), as often observed, but also, as suggested by the current results, could play a causal role in the unfolding of real sleep difficulties among these children, who may become increasingly less able to self‐regulate at night without the intervention of a caregiver (Sadeh et al, ). Hence, although our findings are clearest in the suggestion of a role for secure parent‐child attachment in the development of adequate sleep regulation among toddlers, we would tentatively suggest that child dependency generally, or resistant attachment specifically, may deserve further attention.…”
Section: Discussionsupporting
confidence: 58%
“…Studies in the field have largely relied on subjective measures (maternal reports) of sleep. Most of these studies suggest that mothers of resistant children report more sleep problems in their children than mothers of children characterized by secure or avoidant attachment (Beijers, Janser, Riksen‐Walraven, & de Weerth, ; McNamara, Belsky, & Fearon, ; Morrell & Steele, ; Zentall, Braungart‐Rieker, Ekas, & Lickenbrock, ). Children with resistant attachment are characterized by dependency, signaling of distress, and poor soothing abilities (Ainsworth, Blehar, Waters, & Wall, ).…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…Previous work stemming from these data include three publications examining attachment but not infant SFP responses (Lickenbrock, Braungart-Rieker, Ekas, Zentall, Oshio, & Planalp, in press; Planalp & Braungart-Rieker, 2013; and Zentall, Braungart-Rieker, Ekas, & Lickenbrock, 2012), one examining second-by-second associations between affective and behavioral responses within the SFP but not attachment (Ekas, Lickenbrock, & Braungart-Rieker, 2013), and two looking neither at attachment nor infant SFP responses (Ekas, Braungart-Rieker, Lickenbrock, Zentall, & Maxwell, 2011; Planalp, Braungart-Rieker, Lickenbrock, & Zentall, S. (in press). For the purposes of this study, data from all but the last visit were examined.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Zentall and colleagues (Zentall, Braungart-Rieker, Ekas, & Lickenbrock, 2012) found that night waking as reported by parents at 7 months of age was unrelated to attachment (measured at 12 months of age). However, at 12 months of age, securely attached infants had fewer parent-reported night-awakenings than their insecure counterparts.…”
Section: Attachment and Sleepmentioning
confidence: 99%